Contribution of B35 Biodiesel to Indonesia’s Renewable Energy Target and Challenges for B40 Implementation - Nurrudin Ahmad; Khaerudin Khaerudin; Jupriyanto Jupriyanto; Aris Haryanto; Rizky Dwiandra Putra (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2025)
Indonesia aims for 23% renewable energy by 2025 and a 29% reduction in greenhouse gas emissions by 2030 under the Paris Agreement. B35 biodiesel, a blend of 35% palm oil-based biodiesel and 65% diesel, is a key strategic solution for this energy transition. This study, using a mixed method approach with regression analysis, analyzed data from the Ministry of Energy and Mineral Resources and Indonesian palm oil industry reports. It aimed to quantify B35's contribution to the renewable energy mix and project outcomes for a potential B40 policy. An in-depth analysis was conducted to identify the success factors and challenges of biodiesel implementation. Results show B35 biodiesel significantly contributes to Indonesia's renewable energy goals, reaching 38% in 2023 and 38.75% in 2024. Its implementation also led to substantial savings of IDR 120.54 trillion in 2023 and IDR 123 trillion in 2024 by substituting fossil fuel imports. Regression projections suggest that B40 biodiesel could further increase renewable energy contributions to 40.7% with a 15.62 million kL production target in 2025. Additionally, biodiesel usage reduces CO₂ emissions by 8-11% compared to conventional diesel. In conclusion, B35 biodiesel plays a vital role, contributing nearly 40% to Indonesia's national renewable energy. For successful B40 implementation and to optimize biodiesel's role in achieving 2025 targets, a stable Crude Palm Oil (CPO) supply, a USD 4.1 billion infrastructure investment, consistent policy frameworks, feedstock diversification, carbon tax implementation, and strong inter-ministerial collaboration are essential.